Heterogeneous Household Responses to Energy Price Shocks - Gert Peersman; Joris Wauters (Center for Economic Studies and ifo Institute (CESifo), 2022)
We use survey evidence on reported spending in hypothetical energy price shock scenarios to study novel features of the price elasticity of energy demand and the marginal propensity to consume (MPC) after paying the energy bill. We find that the price elasticity is significantly larger for price increases than price decreases and diminishes heavily for greater price hikes. The elasticity is also larger for households undertaking major home renovations over the next months, and smaller for families with more appetite to consume. For the MPC, we document greater responses of non-energy consumption when energy prices increase compared to price decreases. MPCs are also larger for households with low income and/or saving buffer, and households reporting their future financial situation is difficult to predict. Finally, we show that targeted price subsidies on energy for Belgian low-income households are much more effective in supporting non-energy consumption than the general VAT reduction on energy prices.
Keywords: D12; E21; H31; Q41; Q43; 330; energy demand; marginal propensity to consume; household heterogeneity